Explanation in The Meaning at Ibn-Al khabbaz, in (Tawjeeh Al-lomaa) (Journal of Hama University, 2020)
This research is being studying Explanationi In  the meaning at Ibn-Al khabbaz, in his explanation of Ibn-Jinne's book (Al-Lomaa), that known as (Tawjeeh Al-lomaa),He began with an introduction that talked about the importance of meaning at Grammarer , followed by a preface to the idea of research, and a quick translation of the Author, and then the main idea of research:  Explanation In  the meaning at Ibn-Al khabbaz,he explained the manifestations of this explanation, and the most important reasons based on meaning, such as the  Security of confusion, The difference, Likeness, Pregnancy on meaning, etc.,He gave examples of each type of reasons, and then the conclusion of the research was a summary of his most important findings, and these findings were described by a glossary of the sources and references on which the research relied on its scientific material.